Micropartículas de alginato obtidas por spray drying para liberação modificada de indometacina - Silva, Bruna Pereira da (2017)
Non-steroidal anti-inflammatory drugs are among the most commonly prescribed drugs in the world. Indomethacin has important anti-inflammatory, analgesic and antipyretic activities, but chronic use may cause ulcerative lesions. For the reduction of side effects caused by conventional drugs, modified release systems have been widely used. Microparticles are systems that can be developed through polymers and are effective in controlled drug delivery. Among the natural polymers we can highlight sodium alginate, which presents biocompatibility, atoxicity and low acid degradation profile, which makes it promising for use in drug delivery systems of various therapeutic classes, among them anti-inflammatories. Thus, the present work aimed to develop, characterize morphologically and physico-chemically and to evaluate the biological activity of alginate microparticles containing indomethacin, to obtain a release system that reduces the side effects. The microparticles were developed by the spray drying method through a schedule with variation of polymer concentration, different solvents for incorporation of the drug and various drying parameters. The characterization was performed through Scanning Electron Microscopy (SEM), particle size and distribution analysis, yield and encapsulation efficiency, X-ray Diffraction (XRD), Fourrier Transformed Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) . Through the analysis it was observed that through the optimization of the method microparticles with spherical morphology, reduced sizes (1-4 μm) were obtained and that the formulations with propylene glycol in the composition showed the greatest encapsulation efficiencies. It was verified that the microparticles presented the same physical-chemical profile as the one presented by the polymer, suggesting the dispersion of the drug in the developed polymer matrices. The best-performing system was selected for biological activity and demonstrated greater anti-inflammatory activity than the drug and lower incidence of ulceration by comparison with the administration of pure indomethacin. Thus, the microparticulate system proved to be a promising candidate for the better anti- inflammatory and gastroprotective activity of indomethacin.